A New Perspective on the Risk of Hypercoagulopathy in Ovarian Hyperstimulation Syndrome Using Thromboelastography. (December 2017) - Zohav, Eyal; Almog, Benny; Cohen, Aviad; Levin, Ishai; Deutsch, Varda; Many, Ariel; Amit, Ami; Cohen, Yoni
Thromboelastography (TEG) provides real-time assessment of hemostasis by measuring the viscoelastic properties, coagulation factor, and platelet activity in whole blood samples. In this prospective case–control study, we wanted to investigate whether blood clot formation assessment, using TEG, can identify a hypercoagulable state in women with severe ovarian hyperstimulation syndrome (OHSS). Thirty-six women who were hospitalized with severe OHSS were allocated to the OHSS group and 32 women undergoing controlled ovarian hyperstimulation but who did not develop OHSS were allocated to the control group. The TEG indices were compared between women with severe OHSS and controls. All the coagulation indices assessed by TEG were significantly different in the OHSS group compared to the controls, depicting a hypercoagulable state. Median coagulation index was 3.6 (interquartile range: 2.80-4.15) and 1.45 (interquartile range: 0.20-2.30) in study group and controls, respectively ( P < .001). Our results show that TEG can be used to depict a hypercoagulable state in women with severe OHSS.